Pemeriksaan Rutin Asam Urat dalam Rangka Pencegahan Timbulnya Arthritis Gout pada Kelompok Usia Produktif di Wilayah Krendang - Arwinder Singh; Alexander Halim Santoso; Jeffrey Saputra Kawi; Edwin Destra; Monika Monika (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
Uric acid is a byproduct of purine metabolism in the body, typically excreted through urine. However, excessive uric acid can lead to the accumulation of crystals in the joints, resulting in gouty arthritis, particularly in individuals of productive age. This article aims to discuss a community service initiative to prevent elevated uric acid levels through routine screenings and education on healthy lifestyles. The initiative employed the PDCA (Plan-Do-Check-Act) approach, encompassing counseling, uric acid level examinations, and iterative evaluations, thereby enhancing public awareness of the importance of maintaining normal uric acid levels and understanding healthy lifestyle practices. Education and early detection of uric acid levels can help the community comprehend actionable steps to reduce the risk of long-term health complications.